Heat waves and pediatric emergency department febrile-related visits - Miguel Ángel Molina Gutiérrez; Belén Tortajada Hernández; Clara Díez-Picazo Garot; María Camacho Gil; María Bellido Gómez; Ferrán Campillo López (Elsevier, 2024)
Background: In recent decades, we have observed an increase in ambient temperature due to the effects of climate change. Objective: In this study, we aimed to determine whether there is a correlation between environmental temperature and urgent consultations of pediatric patients related to febrile processes. Research design and method: We conducted an observational, retrospective, single-center study in the pediatric ED of the Hospital Universitario La Paz, Madrid, Spain. We analyzed visits to the ED for febrile processes during the last heat waves in Madrid. Results: Between 2018 and 2022, seven heat waves were recorded in Madrid. A total of 3967 patients with fever as the main reason for consultation attended during this period. In two of the seven heat waves analyzed, febrile-related visits were higher during the heat alert. The first occurred between 6/11/2022 and 6/16/2022, with 345 febrile-related ED visits, 25.4% more than the previous days and 19.7% more than the following days. During this heat wave, we observed a positive correlation between the maximum temperature recorded and the number of visits to the ED for febrile processes (Rs=0.552; p = 0.018). During the heat wave between 09/07/2022 and 17/07/2022, 362 febrile-related ED visits were 3.1% more than the previous days and 24.9% more than the following days. Conclusion: During recent heat waves in our city, we registered an increase in febrile-related visits compared with non-heat alert periods.